Faktor Faktor yang Mempengaruhi Kepuasan, Kepercayaan, dan Kesetiaan Konsumen Dalam Membeli Produk di Website Online Kaskus - Loo, Richard (Universitas Katolik Widya Mandala Surabaya, 2012)
On today's Internet has become a necessity for many people, because with the Internet people can search and find a variety of information quickly and easily. Concept commonly used in e-commerce is business to business (B2B) and business to consumer (B2C). Kaskus is the largest virtual community forum site and number one in Indonesia. The results of this study is expected to provide information to the e-retailer on the factors that may influence e-customer satisfaction, customer loyalty and e-e-customer trust. The sampling technique used a non-random sampling, with SEM as it’s analysis data. This research shows that the hypothesis H1: user interface proved to affect the quality of e-customer satisfaction, H2: user interface is not shown to affect the quality of e-customer trust, H3: information quality is not proven effect on the quality of e-customer satisfaction, H4: information quality quality no proven effect on e-customer trust, H5: perceived security has not been proven effect on e-customer satisfaction, H6: perceived security has not been proven effect on e-customer trust, H7: perceived privacy proven effect on e-customer satisfaction, H8: perceived shown to affect the privacy of e-customer trust, H9: e-customer satisfaction is not proven effect on e-customer loyalty, H10: e-customer trust shown to affect the e-customer loyalty